Dewetting‐Assisted Patterning of Organic Semiconductors for Micro‐OLED Arrays with a Pixel Size of 1 µm. Issue 4 (16th February 2022) - Zhou, Xiaojie; Cai, Yichen; Xu, Mingsheng; Li, Jianping; Sheng, Chenxu; Zhang, Qiuyi; Qiu, Xinxia; Wang, Wenchong; Xiong, Shisheng; Cong, Chunxiao; Qiu, Zhi‐Jun; Liu, Ran; et al.
Abstract: The emergence of near‐eye displays, such as head‐mounted displays, is triggering a requirement for highly enhanced display resolution. High‐resolution micro‐displays with micro‐organic light‐emitting diodes (micro‐OLEDs) can be a preferential candidate, owing to the mature industrialization of OLEDs along with the advantages of flexibility, light weight, and ease of processing. However, micro‐OLEDs with pixel sizes down to micrometers are difficult to be achieved using conventional techniques such as fine metal mask evaporation and lithography. Here, a solution‐processing approach to pattern organic semiconductors (OSCs) for micro‐OLED arrays with the assistance of templated dewetting is demonstrated. Solvents containing organic functional materials are dewetted on the surface with hydrophobic/hydrophilic patterns to form ordered droplet arrays using dip‐coating. Subsequently, patterned OSC films are produced by effectively controlling solvent evaporation. Micro‐OLED arrays with a pixel size down to 1 µm are successfully fabricated by further deposition of emitting/electron transport layers and top electrodes. This approach can open an avenue for low‐cost manufacturing of flexible and high‐resolution micro‐displays. Abstract : High‐resolution microdisplays are usually hard to be achieved for conventional patterning technologies including metal mask evaporation and lithography. Herein, micro‐OLED arrays with a 1‐μm pixel size are obtained with the assistance of templated dewetting, without the influence of the coffee ring effect that usually exists in solution‐processed patterns. These may open an avenue for the manufacturing of high‐resolution microdisplays.